2009
DOI: 10.1158/0008-5472.sabcs-5152
|View full text |Cite
|
Sign up to set email alerts
|

Breast conservation: factors predictive of residual disease following reoperation for narrow surgical margins.

Abstract: #5152 Introduction:
 Ensuring pathologically tumor free surgical margins reduces local recurrence rates following breast conserving surgery for breast cancer or DCIS. There is no general agreement regarding the definition of a clear margin but units with an agreed policy report reduced local recurrence rates. In our unit all patients with a surgical clearance of <5mm are offered further surgery either by mastectomy or by re-excision. We have examined factors that may predict re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Thus Pittinger and colleagues found residual disease in 44% of cases with involved margins, 24% of cases with free margins of B3 mm, and no further tumour in wider excision/mastectomy specimens when the free margin exceeded 3 mm [62]. An analysis of data from the authors' unit has shown that residual disease is found in 60% of patients with involved margins, 40% of those with negative margins up to 2 mm, and only 6% for patients with a margin of 2-5 mm (OR: 2-5 mm margin versus involved margin = 0.05; p = 0.004) [63]. Other investigators have similarly reported a low probability of finding residual disease upon further resection when the margin of clearance is at least 2 mm (2.3%), compared with one third of cases where the clearance is between 0.1 and 0.9 mm [56].…”
Section: Surgical Marginsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus Pittinger and colleagues found residual disease in 44% of cases with involved margins, 24% of cases with free margins of B3 mm, and no further tumour in wider excision/mastectomy specimens when the free margin exceeded 3 mm [62]. An analysis of data from the authors' unit has shown that residual disease is found in 60% of patients with involved margins, 40% of those with negative margins up to 2 mm, and only 6% for patients with a margin of 2-5 mm (OR: 2-5 mm margin versus involved margin = 0.05; p = 0.004) [63]. Other investigators have similarly reported a low probability of finding residual disease upon further resection when the margin of clearance is at least 2 mm (2.3%), compared with one third of cases where the clearance is between 0.1 and 0.9 mm [56].…”
Section: Surgical Marginsmentioning
confidence: 99%
“…These loco-regional effects of systemic treatments will tend to reduce the impact of surgery and radiotherapy on mortality; the chance of any persistent or recurrent disease in the breast and regional nodes acting as a source of distant disease will be minimized, and patients will be more likely to succumb Fig. 12 Relationship of local recurrence to margin status (defined as ''positive'' and ''negative'') [63] World J Surg (2012) 36:1460-1474 1471 from competing risks of pre-existent distant metastases. Techniques of gene profiling can potentially characterize the biology of individual tumors and provide a molecular ''portrait,'' which can guide treatment strategies.…”
Section: Local Treatments At Presentation Versus Relapsementioning
confidence: 99%